2007
DOI: 10.1590/s1516-14392007000300011
|View full text |Cite
|
Sign up to set email alerts
|

High temperature oxidation resistance of rare earth chromite coated Fe-20Cr and Fe-20Cr-4Al alloys

Abstract: Doped lanthanum chromite has been used in solid oxide fuel cell (SOFC) interconnects. The high costs involved in obtaining dense lanthanum chromite have increased efforts to find suitable metallic materials for interconnects. In this context, the oxidation behavior of lanthanum chromite coated Fe-20Cr and Fe-20Cr-4Al alloys at SOFC operation temperature was studied. Isothermal oxidation tests were carried out at 1000 °C for 20, 50 and 200 hours. Cyclic oxidation tests were also carried out and each oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The use of reactive elements, especially rare earths (RE) to improve high temperature oxidation resistance of chromium dioxide and alumina forming alloys is quite well documented. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] The improvements are in the form of reduced oxidation rates and increased scale adhesion. The RE can be added to the alloy in elemental form or as oxide dispersions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of reactive elements, especially rare earths (RE) to improve high temperature oxidation resistance of chromium dioxide and alumina forming alloys is quite well documented. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] The improvements are in the form of reduced oxidation rates and increased scale adhesion. The RE can be added to the alloy in elemental form or as oxide dispersions.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be applied as an oxide coating to the alloy surface. [3][4][5][6][7]15 Various mechanisms have been proposed to explain the effect of reactive elements in improving oxidation resistance and the most widely accepted mechanism attributes it to segregation of the reactive elements to the interface or to the oxide scale grain boundaries and blocking of Cr ion diffusion though the oxide scale [8][9][10][11] Studies carried out by Seo et al, about the effect of addition of Ce, La and Y to a Fe-22Cr-0.5Mn alloy on the oxidation behavior of the alloy at 800 °C, indicated that Y was the most effective element to reduce the growth rate of the oxide scale. 12 In recent years a number of studies have been carried out to exploit the benefits of rare earth additions on oxidation behavior of chromium dioxide and alumina forming alloys.…”
Section: Introductionmentioning
confidence: 99%